(untitled) - Sara Wang, Maria Shu Hong Bee Abdullah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In this paper, Formulaic Sequences (FS) over the past ten years are reviewed to provide some insights on its usage in the process of teaching and learning English language in China. It identifies three main features. Firstly, the general trends of FS, Secondly, the characteristics of development of FS in various fields. Thirdly, the use of FS and the teaching of FS. Finally, the paper puts forward some suggestions on the use of formulaic sequence on teaching and learning foreign language in mainland China?